Quartet repertoire fortrombone Baritone third part, tuba fourth part - KOEPKE, Paul [et.al] (Rubank Inc., 1957)
Scherzo capricenWhere'er you walknEquale No.2nGreenwoodnTwo PiecesnSouthlandnCanzonettanThe OctopusnCaro Mio BennjamboreenHunting SongnLight FantasticnCragged PassnBallet Harlequins